Italian Policy toward Libya after 2011 (Journal of Human Sciences, 2026)
The internal Libyan conflict that emerged after the events of February 2011 increased security and economic risks for Italy , prompting it to take  a number of  positions               affecting Libya domestic affairs.  The Italian stance is considered the most engaged in the libyan issue due to the security, economic and political considerations that link the two countries. The primary driver behind these Italian positions has been Italy's own interests, which were significantly affected after the events of 2011. The study aimed to shed light on Italy's policy in Libya after the events of 2011, focusing on its key dimensions, namely securing   oil, and gas, ensuring security, and regaining influence one of the main factors behind Italy's growing interests in resolving the Libyan conflict. It also seeks to analyze the various challenges facing Italian policy in Libya after the events of 2011.)